2018
DOI: 10.1111/srt.12473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sex‐related changes in skin topography and structure using innovative skin testing equipment

Abstract: Non-invasive methods of skin testing using new and advanced equipment have provided a possibility of objective parametrization and evaluation of sex-related changes in skin topography and structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…In accordance with the findings of Dąbrowska et al, (2018), the present results revealed significant differences in the skin surface and structure between males and females . These authors found that the skin of women had more abundant superficial skin lines and wrinkles in comparison with male skin, which was in agreement with previous literature reporting that men's skin had a lower number of wrinkles .…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the findings of Dąbrowska et al, (2018), the present results revealed significant differences in the skin surface and structure between males and females . These authors found that the skin of women had more abundant superficial skin lines and wrinkles in comparison with male skin, which was in agreement with previous literature reporting that men's skin had a lower number of wrinkles .…”
Section: Discussionsupporting
confidence: 93%
“…All equipment was purchased from Courage + Khazaka electronic GmbH (Köln, Germany). The importance of technical possibilities of the above-mentioned devices concerning selected skin parameters have been described comprehensively in the authors’ previous publications [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The numbers of enlarged facial pores were determined by applying the “small” filter, as the small filter of the Antera 3D® is well correlated with visual perception and sensitive enough to distinguish changes caused by application of cosmetic products 27 . An Ultrascan UC22 (Courage + Khazaka Electronic) was used to evaluate the dermal density of the skin before and after application of products 28 . A Vivascope 1500 (Caliber ID Rochester) confocal laser scanning microscope (CLSM) was used to examine the inner skin structures from the stratum corneum to the epidermal‐dermal interface in vivo noninvasively.…”
Section: Methodsmentioning
confidence: 99%
“…27 An Ultrascan UC22 (Courage + Khazaka Electronic) was used to evaluate the dermal density of the skin before and after application of products. 28 A Vivascope 1500 (Caliber ID Rochester) confocal laser scanning microscope (CLSM) was used to examine the inner skin structures from the stratum corneum to the epidermal-dermal interface in vivo noninvasively. CLSM uses a laser source with a wavelength of 830 nm, illumination power up to 22.1 mW on the object, and water-based gel as the immersion media.…”
Section: Instrumentsmentioning
confidence: 99%